Pola Pemukiman Komunitas Budaya Megalitik Di Desa Muak, Dataran Tinggi Jambi - Tri Marhaeni S. Budisantosa (Balai Arkeologi Sumatera Utara, 2015)
The dispersion of archaeological sites at Muak Village in Jambi Highland forms a spatial grouping of sites of a community in the past. However, the settlement pattern and local geographical condition, which influenced it, has yet to be recognized. To solve the problem, three phases of analyses were performed. First, specific or descriptive was carried out to identify artifacts. Second, the contextual analysis was conducted to know the functions of the artifacts and sites. Third, the semi-micro spatial analysis was done to reveal the site to site relationships as well as a relation between a site and the surrounding geographical environment. Based on those analyses can be identified that the megalithic settlement at Muak Village consisted of ritual, habitation, and urn burial sites. The layout of those sites is a ritual site encircled by the habitation site, while the urn burial site is located outside the habitation area. Moreover, the relation between the sites and the surrounding environment is that the ritual and habitation sites are located on hill ridges, while the urn burial site is on hill slope or valley.